From gelatinous to muscle food chain: rock cod Patagonotothen ramsayi recycles coelenterate and tunicate resources on the Patagonian Shelf. Issue 5 (6th September 2013) - Arkhipkin, A.; Laptikhovsky, V.
<x xml:space="preserve">Abstract</x> Stomach contents of 4808 fishes of 20 species caught in the eastern part of the Patagonian Shelf between 1999 and 2012 were analysed to assess dietary contributions of gelatinous plankton resources. Gelatinous plankton occurred in diets of seven species with two species, Patagonotothen ramsayi and Squalus acanthias, having >10% ctenophores in their diet. Consumption of gelatinous plankton was important in P. ramsayi and was strikingly seasonal, with maximum occurrence (up to 46% of non‐empty stomachs) in late summer to autumn. Ctenophores were most abundant in P. ramsayi of 25–34 cm total length, LT, whereas salps were more frequent in larger >35 cm LT individuals. In winter to spring, occurrence of gelatinous plankton in diets was minimal, reflecting their overall seasonal abundance in the ocean. The recent increase in abundance of P. ramsayi has enabled the species to recycle a significant proportion of the ecosystem production from gelatinous dead end to the main muscular food chain via seasonal reliance on ctenophores, jellyfish and tunicates. This additional influx of production that has been diverted from the gelatinous food chain favours the increase in abundance of several piscivorous top predators and affects the trophic web structure of the Patagonian Shelf ecosystem.